Human Tissues Contain CD141(hi) Cross-Presenting Dendritic Cells with Functional Homology to Mouse CD103(+) Nonlymphoid Dendritic Cells - Haniffa, Muzlifah (Cell Press, 2012)
Dendritic cell (DC)-mediated cross-presentation of exogenous antigens acquired in the periphery is critical for the initiation of CD8(+) T cell responses. Several DC subsets are described in human tissues but migratory cross-presenting DCs have not been isolated, despite their potential importance in immunity to pathogens, vaccines, and tumors and tolerance to self. Here, we identified a CD141(hi) DC present in human interstitial dermis, liver, and lung that was distinct from the majority of CD1c(+) and CD14(+) tissue DCs and superior at cross-presenting soluble antigens. Cutaneous CD141(hi) DCs were closely related to blood CD141(+) DCs, and migratory counterparts were found among skin-draining lymph node DCs. Comparative transcriptomic analysis with mouse showed tissue DC subsets to be conserved between species and permitted close alignment of human and mouse DC subsets. These studies inform the rational design of targeted immunotherapies and facilitate translation of mouse functional DC biology to the human setting.